Impacts of Instructional Materials in Enhancing Biology Concepts Retention among Secondary School Students in Izzi, Ebonyi State, Nigeria - Lucy Aja; Igwe Chinedu Okuku; Tukur Muhammad; Iruka John Elom; Lubega Mohammad; Chinyere Grace Ezeonwumelu; Kingsley Ikechukwu Oko (Scientia Publica Media, 2026)
This study examined how instructional materials influence secondary school students’ ability to retain biology concepts. The study used a descriptive survey research approach and was directed by three research questions. Six hundred and two (602) SSII students comprised the study population, and 240 responders comprised the sample size using Slovin’s formula for sample size determinations. The students were sampled using a simple random sampling technique. The tool for gathering data was a structured questionnaire. Three test experts with backgrounds in measurement and evaluation and biology teaching face-validated the questionnaire. The quantitative data were analyzed using mean scores and frequency distribution tables. The study’s conclusions showed, among other things, that the effective and adequate use of instructional materials available for teaching and learning influences secondary school students’ retention of biology concepts. This is because such materials help in the recall of certain concepts and the recognition of biological principles. Additionally, because they make biology easier to study, using instructional materials improved the effectiveness of biology topics taught and learned. Based on the findings, the researcher recommends that students, teachers, educational administrators, and policymakers place more value on using instructional materials in biology classrooms. Government agencies, Ministries of Education, and educational agencies should supply instructional materials to secondary schools to improve the quality of teaching and learning of biology, and biology teachers should participate in seminars and workshops on the use of instructional materials to stay current on their knowledge and improve their effectiveness as teachers.